Hi

Can you tell me if my solution is correct?

thanks

John

Evaluate using the method of partial fractions:

$\displaystyle \frac {10.dx}{(2x-6)(x+5)}$

This gives

$\displaystyle 10=A.(x+5)+B.(2x-6)$

Making

$\displaystyle x=-5$

$\displaystyle \frac{1}{-6}=B$

$\displaystyle x=3$

$\displaystyle \frac{5}{4}=A$

This results in an separate integrations of:

$\displaystyle 5\int \frac{1}{4.(2x-6)}- \int \frac{1}{6(x+5)}$

This solves to give;

$\displaystyle \frac{5}{4} ln(2x-6)-\frac{1}{6}ln(x+5)+C$